Use of VaserTM plus liposuction in body contouring surgery - William Seidel; Caio Pundek Garcia (Revista Brasileira de Cirurgia Plástica, 2020)
Introduction: Body contouring surgery is among the most requested surgical procedures in cosmetic surgery. Mentz was the first to perform superficial liposuction to define the abdominal muscles in male patients. However, Scuderi first popularized the use of continuous ultrasound to produce fat fragmentation in lipoplasty. Ultrasound, when applied internally to adipose tissue using a probe or metal cannula, breaks cells through three mechanisms: cavitation, thermal effect, and direct mechanical effect. Methods: Since November 2018, 50 patients with an indication for body liposuction performed the procedure with the help of the third-generation ultrasound equipment (VASER). Results: During the period between November 2018 and March 2019, 50 patients with a surgical indication underwent body contour liposuction using third-generation VASER technology. Of this universe of patients, 96% were women (47), with patients with an average age of 35 years (21-54). Conclusion: The association of VASER with liposuction is a safe and reproducible technique that has the advantage of improving the result of liposculpture. Good aesthetic results were achieved, with an athletic and more natural contour.